Work, life, and the gender effect: Perspectives of ACVIM Diplomates in 2017. Part 1—Specialty demographics and measures of professional achievement. (17th August 2020) - Morello, Samantha L.; Colopy, Sara A.; Chun, Ruthanne; Buhr, Kevin A.
Abstract: Background: Barriers to achieving work‐life balance, as well as gender‐based differences, exist in the male‐dominated surgical specialty in veterinary medicine. Similar information does not exist for the more feminized American College of Veterinary Internal Medicine (ACVIM). Hypothesis/Objectives: To provide data on the professional and personal lives of Diplomates of the ACVIM so as to help define the state of the specialty, including gender‐related differences, and identify areas requiring intervention to improve work‐life balance. Sample: A total of 896 surveys (781 completed) of Diplomates of the ACVIM, including cardiology, large animal internal medicine, neurology, oncology, and small animal internal medicine. Methods: An 82‐item online survey was distributed in February 2017 to ACVIM Diplomates via their respective ACVIM listserv. Participation was voluntary. Results: Thirty percent of the total ACVIM registered membership responded and 26% completed surveys; 25% were men and 75% were women. Specialists in academia worked significantly more hours, with larger numbers of diplomates per specialty section, and made less money compared with those in private practice. Women were less likely to report full‐time employment, practice ownership, or higher academic rank, and reported 20% lower income overall (after adjustment for relevant factors) as compared with men. Men and women differed in their subjective assessment of the effect of gender in the workplace. Eighty‐three percent of respondents were somewhat satisfied or better with their career. Conclusions and Clinical Importance: Specialization in the ACVIM is a satisfying and potentially profitable career. However, despite a highly feminized workforce, significant gender‐related imbalances are evident.